Technical and economic analysis of biogas and solar photovoltaic (PV) hybrid renewable energy system for dairy cattle barns - Kirim, Yavuz; Sadikoglu, Hasan; Melikoglu, Mehmet (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Novel to this study, modular hybrid renewable energy systems comprising of biogas and solar photovoltaic (PV) are designed for various dairy cattle barns located in Konya, Erzurum and I_zmir provinces of Turkey. It is estimated that the grid-connected system including PV and biomass are more feasible than the stand-alone biomass system in terms of net present cost, return on investment, cost of energy and annual worth. Thirteen independent variables are used to predict the contribution of electricity generation from the modular hybrid renewable energy systems to Turkey's gross domestic product. Optimum annual worth of different cattle barns is chosen as an independent econometric variable. Linear, ridge, lasso and elastic net regression models are generated. Among these regression models, ridge regression gives the highest coefficient of determination as 0.92, and the lowest root mean squared error value of 0.463 (million $). The lowest net present cost values of grid-connected barn systems with five different cattle capacities are found as $36942, $54219, $270119, $721516 and $3097716, respectively. It is found that total installed cost of solar energy has the strongest effect on the share of electricity generation in terms of the effect on the gross domestic product, which is calculated as 97%. (c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Hybrid renewable energy system; Feasibility analysis; Net present cost; Regression models; POWER-GENERATION; RURAL ELECTRIFICATION; BIOMASS; FEASIBILITY; OPTIMIZATION; BIOENERGY; DESIGN; Science & Technology - Other Topics; Energy & Fuels